A SYNTACTIC ANALYSIS ON THE ENGLISH TRANSLATION OF SURAH AL QIYAMAH USING TREE DIAGRAMS - Alfini Iasya Putri (LET: Linguistics, Literature and English Teaching Journal)
In this research, the researcher analyzed syntactical patterns of the whole verses (ayah) in the English translation of surah Al Qiyamah, which has 40 ayah, using tree diagrams theory to be able drawing and seeing hierarchical syntax structure of the verses in the surah. After analyzing the data, the researcher finally found twenty four syntactic patterns of the surah: there are sixteen patterns of sentence and eight patterns of phrases. The phrases patterns are : a) the pattern of noun phrase appears in one position, b) the patterns of verb phrase appear in three position, c) the patterns of adjective phrase appear in two position, d) the pattern of prepositional phrase appears in one position, and e) the pattern of complement phrase appears in one position